In-situ carbon-coated multi-cation doped lithium manganese iron phosphate and preparation method thereof
The in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate preparation method solves the problems of conductivity and structural stability of lithium manganese iron phosphate materials, and achieves a high-efficiency improvement in electrochemical performance, making it suitable for lithium-ion battery cathode materials.
Patent Information
- Application Number
- CN202411359308.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-27
AI Technical Summary
In existing technologies, lithium manganese iron phosphate materials have poor conductivity and structural stability, resulting in poor cycle stability and rate performance as cathode materials for lithium-ion batteries. Furthermore, traditional preparation methods make it difficult to achieve a uniform distribution of multi-element doping elements.
An in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate was prepared by synthesizing a metal-organic framework precursor via a solvothermal method, achieving atomic-level uniform distribution of the three doped metal elements, and forming an N-doped carbon coating layer after high-temperature sintering, thereby optimizing the electronic structure and improving the material properties.
The conductivity and compaction density of lithium manganese iron phosphate were improved, which enhanced the first discharge efficiency, rate performance and cycle performance of lithium-ion battery cathode materials, and significantly improved structural stability.
Smart Images

Figure CN119263245A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery electrode materials, and more specifically, relates to an in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate and a preparation method thereof. Background Art
[0002] In recent years, lithium iron phosphate (LiFePO4, LFP) has been increasing its market share in the lithium-ion battery cathode material market due to its advantages such as high safety performance, low cost, and long cycle life. However, lithium iron phosphate has a relatively low operating voltage (3.4V), which makes the energy density of lithium iron phosphate batteries (580Wh / kg) close to the limit. Although lithium manganese phosphate (LiMnPO4, LMP) cathode materials with the same olivine structure have a higher operating voltage (4.1V) and better energy density (701Wh / kg), the Mn in LMP is 3+ The induced Jahn-Teller effect greatly affects the structural stability of the material, and its poor Li + Diffusion coefficient and conductivity hinder its industrial application as a high energy density lithium ion battery positive electrode material. x Mn 1-x PO4, 0<x<1), which has a theoretical mass specific capacity similar to that of LFP, and also has a specific capacity corresponding to Mn at 4.1V. 3+ / Mn 2+ The high voltage platform generated by the redox couple and Fe 3 + / Fe 2+ The voltage platform generated by the redox couple increases the working voltage and energy density of the material, making it a promising new type of lithium-ion battery cathode material. However, as the proportion of manganese in the lattice increases, the conductivity of the material is greatly reduced, and the Mn 3+ The Jahn-Teller effect and manganese dissolution problems caused by this have become increasingly prominent, resulting in poor cycle stability and rate performance of the material.
[0003] Carbon coating and doping modification methods are used to solve the above problems. Among them, the carbon coating strategy can effectively improve the conductivity of phosphate system cathode materials. Metal cation doping can optimize the conductivity and ion diffusion capacity of materials from the inside of the lattice at the atomic level, improve structural stability, and inhibit Mn 3+The Jahn-Teller effect and manganese dissolution induced by the cation doping can improve the cycle stability and rate performance of lithium iron manganese phosphate, while inhibiting the manganese dissolution rate of the positive electrode material. Common doping elements in positive electrode materials include: Mg, Ti, V, Co, Ni, Cr, Zn, Cu, Zr, Nb, etc. The modification effect of single metal element doping on positive electrode materials is limited. The use of two or more metals to simultaneously dope positive electrode materials can make up for the limitations of single doping element modification. However, the current traditional method for preparing cation-doped lithium iron manganese phosphate is mainly based on the solid phase method, which is to mix the iron source, manganese source, lithium source, phosphorus source, carbon source and dopant and sinter them. Its preparation method makes it easy for multiple doping elements to not be evenly distributed in the material, and it is easy to form an inactive layer on the surface of the material, which in turn causes the lithium iron manganese phosphate positive electrode material to have poor conductivity and poor structural stability, and poor performance in terms of capacity retention, rate performance, compaction density, etc. Summary of the invention
[0004] In order to solve the above-mentioned defects of the prior art, the primary purpose of the present invention is to provide a method for preparing in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate, thereby obtaining high-density lithium manganese iron phosphate and improving its conductivity.
[0005] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0006] A method for preparing in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate comprises the following steps:
[0007] S1. In an inert atmosphere, dissolving an iron source, a manganese source, a doping metal salt A, a doping metal salt B and a doping metal salt C in a solvent to obtain a solution I;
[0008] S2. In an inert atmosphere, an organic ligand for forming a metal-organic framework, a surfactant and a solvent are uniformly mixed to obtain a solution II;
[0009] S3. After mixing solution I and solution II, an alkali solution is added to adjust the pH value of the solution to 7-9, reacting in an inert atmosphere to obtain a mixed slurry, and then performing solid-liquid separation and washing to obtain a metal-organic framework precursor;
[0010] S4. The metal-organic framework precursor obtained in step S3 is mixed with a lithium source and a phosphorus source, subjected to grinding treatment, spray drying, and calcined under an inert atmosphere to obtain in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate;
[0011] The general formula of the metal-organic framework precursor is Mn x Fe 1-x-a-b-c A a B b C c-MOF, wherein 0<x<1, 0<a<0.04, 0<b<0.04, 0<c<0.04, a+b+c=0.05; A, B, and C are respectively one of the doped metal elements Mg, Ti, V, Co, Ni, Cr, Zn, Cu, Zr, and Nb, and A, B, and C are different from each other.
[0012] The present invention synthesizes a ternary metal cation-doped manganese-iron-based metal-organic framework Mn by a solvothermal method x Fe 1-x-a-b-c A a B b C c -MOF, and then used it as a precursor to react with lithium source and phosphorus source to synthesize high-performance lithium manganese iron phosphate. Since the metal-organic framework is a three-dimensional skeleton with periodic distribution of atoms, Mn x Fe 1-x-a-b-c A a B b C c -The elements in MOF are evenly distributed, and the lithium manganese iron phosphate prepared with it as a precursor can achieve atomic-level uniform distribution of iron, manganese metal elements and three doped metal cations, which is conducive to giving full play to the synergistic effect between the three doped metal elements, improving the structural stability of the material, and thus optimizing the electrochemical properties of lithium manganese iron phosphate.
[0013] Furthermore, the general formula of the metal-organic framework precursor is Mn x Fe 1-x-a-b-c A a B b C c -MOF, wherein 0<x<1, 0<a<0.04, 0<b<0.04, 0<c<0.04, a+b+c=0.05; A, B, C are respectively one of the doped metal elements Mg, Ti, V, Co, Zn, Nb, and A, B, C are different from each other.
[0014] Furthermore, the organic ligand in step S2 is one or more of 4-aminobenzoic acid, 2-aminoterephthalic acid, melamine, imidazole, triazole, benzimidazole, ethylenediamine, ethylenediaminetetraacetic acid, triethylamine, nitrogen tetroxide, 2,2'-bipyridine, 2,4'-bipyridine, 1,10-phenanthroline, 2,6-pyridinedicarboxylic acid, and triethylenediamine.
[0015] The organic ligand in the present invention is a nitrogen-containing organic ligand, which is used to prepare a nitrogen-containing metal-organic framework. In the subsequent stage sintering process, the nitrogen-containing metal-organic framework can be used as a nitrogen source and a carbon source to in-situ generate an N-doped carbon layer on the phosphate surface. The in-situ non-metallic doping formed by the strongly electronegative nitrogen atoms can induce the formation of an electron-deficient structure in the carbon skeleton, thereby optimizing the electronic structure and enhancing the conductivity of the material, which is beneficial to Li + Combined with N atoms to optimize lithium storage performance.
[0016] Furthermore, in step S2, the ratio of the amount of the organic ligand to the total amount of the iron salt, the manganese salt and the metal cation doped with the metal cation salt is (0.5-5): (0.5-5).
[0017] Furthermore, the surfactant in step S2 is one or more of cetyltrimethylammonium bromide, sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, polyvinyl pyrrolidone, sodium lauryl sulfate, lithium dodecylbenzene sulfonate, and polyethylene glycol.
[0018] Furthermore, the molar ratio of the surfactant to the organic ligand in step S2 is (0.1-0.6):(1-15).
[0019] Furthermore, the solvent in step S2 is dimethylformamide and / or anhydrous ethanol and / or ultrapure water. Preferably, the solvent is a mixture of dimethylformamide, anhydrous ethanol and ultrapure water in a volume ratio of 1:1:1.
[0020] Furthermore, the inert atmosphere in step S2 is nitrogen and / or argon.
[0021] Furthermore, in step S4, the molar ratio of the lithium source, the phosphorus source and the metal source in the metal-organic framework precursor is Li:P:(Fe+Mn+A+B+C)=0.95-1.15:0.95-1.15:1.
[0022] Furthermore, in step S4, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium silicate, lithium sulfate, lithium phosphate, lithium orthosilicate, lithium permanganate, lithium metaphosphate, lithium fluoride, lithium bromide, lithium oxide, lithium nitride, lithium sulfide, lithium oxalate, lithium formate, lithium octanoate, lithium citrate, lithium salicylate, lithium trifluoroacetate, lithium acetoacetate, lithium difluorophosphate, lithium hexafluorophosphate, lithium benzoate, lithium pyruvate, lithium acetate, lithium methoxide, and lithium ethoxide.
[0023] Furthermore, the phosphorus source in step S4 is one or more of ammonium dihydrogen phosphate, ammonium phosphate, sodium pyrophosphate, ammonium hypophosphite, ammonium polyphosphate, ammonium hexafluorophosphate, lithium dihydrogen phosphate, lithium phosphate, diammonium hydrogen phosphate, sodium phosphite, sodium metaphosphate, sodium tripolyphosphate, and sodium hexafluorophosphate.
[0024] Furthermore, the calcination treatment in step S4 is to heat to 350-550° C. at a heating rate of 0.5-20° C. / min for low temperature sintering, and then heat to 650-950° C. for high temperature sintering.
[0025] Furthermore, the low-temperature sintering time is 0.5 to 10 hours.
[0026] Furthermore, the high temperature sintering time is 5 to 15 hours.
[0027] In some embodiments of the present invention, in step S4, the heat preservation sintering is followed by air flow crushing and screening to obtain in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate.
[0028] Furthermore, the inert atmosphere in S4 is nitrogen and / or argon, and further, the oxygen content is controlled to be less than 10 ppm.
[0029] Furthermore, the grinding process in step S4 is performed by wet ball milling, specifically, the metal-organic framework precursor obtained in step S3, the lithium source, the phosphorus source, ethanol and ultrapure water are mixed to prepare a slurry, and the slurry is placed in a sand mill and ground to a slurry particle size of 0.28 μm ≤ D 50 ≤0.3μm. Wherein, the volume ratio of ethanol to ultrapure water is 1:1; and the solid content of the slurry is 30-40%.
[0030] Furthermore, the spray drying in step S4 is specifically to feed the ground slurry into the spray drying system, and the control system sets the air inlet temperature to 210-250°C and the air outlet temperature to 110-120°C, and adjust the feed amount according to the particle size of the spray-dried material and the air outlet temperature to obtain the spray powder. Furthermore, the particle size of the spray-dried material is 22μm≤D 50 ≤25μm.
[0031] Furthermore, the reaction temperature in step S3 is 80-120°C.
[0032] Furthermore, the reaction time in step S3 is 4 to 30 hours.
[0033] Furthermore, the alkaline solution in step S3 is one or more of NaOH solution, KOH solution, and ammonia water.
[0034] Furthermore, the solution used for washing in step S3 is a mixed solution of dimethyl diformamide, anhydrous ethanol and ultrapure water (V:V:V=1:1:1).
[0035] Furthermore, the doped metal salt A, the doped metal salt B, and the doped metal salt C in step S1 are respectively one of any soluble magnesium salt, titanium salt, vanadium salt, cobalt salt, nickel salt, chromium salt, zinc salt, copper salt, zirconium salt, and niobium salt known in the art, and the metal cations of the doped metal salt A, the doped metal salt B, and the doped metal salt C are different from each other.
[0036] The iron source and manganese source used in the present invention may be any one or more iron salts and manganese salts known in the art for preparing positive electrode active materials.
[0037] Furthermore, the iron source in step S1 is one or more of ferric chloride, ferrous sulfate, ferrous chloride, ferric nitrate, ferric acetate, ammonium ferric sulfate, ferric citrate, and ferrous oxalate.
[0038] Furthermore, the manganese source in step S1 is one or more of manganese chloride, manganous sulfate, manganese nitrate, manganese carbonate, manganese acetate, and manganese oxalate.
[0039] Further, the solvent in step S1 is dimethyl diformamide and / or anhydrous ethanol, preferably, the solvent is a mixture of dimethyl diformamide and anhydrous ethanol in a volume ratio of 1: 1. Further, the inert atmosphere in step S1 is nitrogen and / or argon.
[0040] Another object of the present invention is to provide an in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate prepared by the above preparation method.
[0041] Furthermore, the compaction density of the in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate is ≥2.46 g / cm 3 , powder resistance ≤10.42Ω·cm.
[0042] Another object of the present invention is to provide a positive electrode sheet, which comprises the above-mentioned in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate.
[0043] Furthermore, the positive electrode sheet further includes a conductive current collector, a binder, a conductive agent, etc. In some embodiments of the present invention, the conductive current collector may be any conductive current collector for a positive electrode known in the art, such as aluminum foil or carbon-coated aluminum foil; the binder may be any binder known in the art, such as sodium hydroxycellulose, polyvinylidene fluoride, styrene-butadiene rubber or one or more thereof; the conductive agent may be any conductive agent known in the art, such as acetylene black, graphene, carbon nanotubes or one or more thereof.
[0044] Another object of the present invention is to provide a battery, comprising the above-mentioned positive electrode sheet.
[0045] Furthermore, the battery also includes a negative electrode sheet, a separator located between the positive electrode sheet and the negative electrode sheet, and an electrolyte.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The present invention introduces three types of metal cations when preparing a manganese iron-based metal-organic framework, uses them as precursors to prepare lithium iron manganese phosphate, realizes co-doping modification of the three metal cations, and makes it have excellent electrochemical properties as a positive electrode material for lithium ion batteries. The present invention uses a manganese iron-based precursor doped with three metal cations to simultaneously form in-situ doping of the three types of metal cations in the lithium iron manganese phosphate lattice, and the three metal cations form an atomic-level uniform distribution in the lithium iron manganese phosphate, which can give full play to the synergistic effect between the doped metal elements selected by the present invention, improve the structural stability of the material, and enhance the rate and cycle stability of the material; in addition, the present invention selects a metal-organic framework precursor prepared by a nitrogen-containing organic ligand, and after high-temperature sintering, a uniform N-doped coated carbon layer is formed in-situ, which can further enhance the conductivity of the material; the preparation method of the present invention is highly compatible with the existing industrial lithium iron phosphate production process equipment, and has industrial application prospects.
[0048] The in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate prepared by the present invention has high conductivity and compaction density. When it is used as a positive electrode material for lithium ion batteries, the first discharge efficiency, rate performance and cycle performance are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a scanning electron microscope image of the in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate according to Example 1 of the present invention. DETAILED DESCRIPTION
[0050] The content of the present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present embodiment are conventional reagents, methods and equipment in the art.
[0051] Example 1
[0052] 1.NH2-Mn 0.6 Fe 0.35 Ti 0.01 Co 0.01 Mg 0.03 -Synthesis of MOF
[0053] First, add 6L of a mixed solution of dimethyldiformamide and 6L of anhydrous ethanol into a high-efficiency sealed synthesis reactor, slowly add 10mol of 2-aminoterephthalic acid and 0.5mol of hexadecyltrimethylammonium bromide into the reactor, introduce nitrogen protective gas, and stir at 100°C and 600rpm for 20min to prepare the bottom liquid in the reactor.
[0054] Secondly, under a nitrogen protective atmosphere, 6 mol of manganese chloride tetrahydrate, 3.5 mol of ferric chloride hexahydrate, 0.1 mol of ammonium titanium oxalate, 0.1 mol of cobalt acetate, and 0.3 mol of magnesium chloride were slowly added to a mixed solution of 6 L of dimethyl diformamide, 6 L of anhydrous ethanol, and 6 L of ultrapure water in sequence, and stirred at room temperature until completely dissolved to prepare a uniform salt solution of manganese, iron, and doped cations I. The above salt solution I was slowly pumped into the reactor using a peristaltic pump. After the salt solution I was completely pumped into the reactor, a 2 mol / L NaOH solution was slowly pumped into the reaction system using a peristaltic pump to control the pH value to 7.5, and stirred thoroughly for 30 minutes. The above system was then reacted at 100 ° C for 12 hours to obtain a mixed slurry II.
[0055] After the reactor was cooled to room temperature, the mixed slurry II was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide, anhydrous ethanol and ultrapure water (V:V:V = 1:1:1) to obtain NH2-Mn 0.6 Fe 0.35 Ti 0.01 Co 0.01 Mg 0.03 -MOF precursors.
[0056] 2. Synthesis of in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate cathode materials
[0057] According to the molar ratio of Li:P:(Fe+Mn+Ti+Co+Mg)=1.05:1:1, lithium dihydrogen phosphate, lithium carbonate, NH2-Mn 0.6 Fe 0.35 Ti 0.01 Co 0.01 Mg 0.03 -MOF precursor, and dispersed in a mixed solution of ethanol and ultrapure water (V:V = 1:1) to prepare a slurry with a solid content of 35%, and the mixed slurry was fully ground in a sand mill to a slurry particle size of 0.28 μm ≤ D 50 When the particle size is less than 0.3 μm, the slurry is transferred to the spray drying equipment. The spray drying system is set with an inlet temperature of 220°C and an outlet temperature of 110°C. According to the outlet temperature and the particle size of the discharge (22 μm ≤ D 50The spray powder was placed in a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content less than 10ppm), and heated to 500℃ for 6h at a heating rate of 3℃ / min, and then heated to 700℃ for 9h.
[0058] After the nitrogen atmosphere box furnace is naturally cooled to room temperature, the sintered powder is subjected to air flow pulverization and then sieved using a sieve to obtain the in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate positive electrode material.
[0059] Example 2
[0060] 1.NH2-Mn 0.7 Fe 0.25 Nb 0.015 Mg 0.015 V 0.02 -Synthesis of MOF
[0061] First, add 6L of a mixed solution of dimethyldiformamide and 6L of anhydrous ethanol into a high-efficiency sealed synthesis reactor, slowly add 10mol of 2-aminoterephthalic acid and 0.5mol of hexadecyltrimethylammonium bromide into the reactor, introduce nitrogen protective gas, and stir at 100°C and 650rpm for 20min to prepare the bottom liquid in the reactor.
[0062] Secondly, under a nitrogen protective atmosphere, 7 mol of manganese chloride tetrahydrate, 2.5 mol of ferric chloride hexahydrate, 0.15 mol of niobium oxalate, 0.15 mol of magnesium chloride, and 0.2 mol of vanadium oxalate were slowly added to a mixed solution of 6 L of dimethyldiformamide, 6 L of anhydrous ethanol, and 6 L of ultrapure water in sequence, and stirred at room temperature until completely dissolved to prepare a uniform salt solution of manganese, iron, and doped cations I. The above salt solution I was slowly pumped into the reactor using a peristaltic pump. After the salt solution I was completely pumped into the reactor, a 2 mol / L NaOH solution was slowly pumped into the reaction system using a peristaltic pump to control the pH value to 7.8, and stirred thoroughly for 30 minutes. The above system was then reacted at 100 ° C for 12 hours to obtain a mixed slurry II.
[0063] After the reactor was cooled to room temperature, the mixed slurry II was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide, anhydrous ethanol and ultrapure water (V:V:V = 1:1:1) to obtain NH2-Mn 0.7 Fe 0.25 Nb 0.015 Mg 0.015 V 0.02 -MOF precursors.
[0064] 2. Synthesis of in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate cathode materials
[0065] According to the molar ratio of Li:P:(Fe+Mn+Nb+Mg+V)=1.05:1:1, lithium dihydrogen phosphate, lithium carbonate, NH2-Mn 0.7 Fe 0.25 Nb 0.015 Mg 0.015 V 0.02 -MOF precursor, and dispersed in a mixed solution of ethanol and ultrapure water (V:V = 1:1) to prepare a slurry with a solid content of 38%, and the mixed slurry was fully ground in a sand mill to a slurry particle size of 0.28 μm ≤ D 50 When the particle size is less than 0.3 μm, the slurry is transferred to the spray drying equipment. The spray drying system is set with an inlet temperature of 230°C and an outlet temperature of 115°C. According to the outlet temperature and the particle size of the discharge (22 μm ≤ D 50 The spray powder was placed in a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content less than 10ppm), and heated to 500℃ for 6h at a heating rate of 2.3℃ / min, and then heated to 680℃ for 9h.
[0066] After the nitrogen atmosphere box furnace is naturally cooled to room temperature, the sintered powder is subjected to air flow pulverization and then sieved using a sieve to obtain the in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate positive electrode material.
[0067] Example 3
[0068] 1.NH2-Mn 0.75 Fe 0.2 Nb 0.015 Zn 0.01 V 0.025 -Synthesis of MOF
[0069] First, add 6L of a mixed solution of dimethyldiformamide and 6L of anhydrous ethanol into a high-efficiency sealed synthesis reactor, slowly add 10mol of 2-aminoterephthalic acid and 0.5mol of hexadecyltrimethylammonium bromide into the reactor, introduce nitrogen protective gas, and stir at 750rpm for 20min at 100°C to prepare the bottom liquid in the reactor.
[0070] Secondly, under a nitrogen protective atmosphere, 7.5 mol of manganese chloride tetrahydrate, 2 mol of ferric chloride hexahydrate, 0.15 mol of niobium oxalate, 0.1 mol of zinc acetate, and 0.25 mol of vanadium oxalate were slowly added to a mixed solution of 6L of dimethyldiformamide, 6L of anhydrous ethanol, and 6L of ultrapure water in sequence, and stirred at room temperature until completely dissolved to prepare a uniform salt solution of manganese, iron, and doped cations I. The above salt solution I was slowly pumped into the reactor using a peristaltic pump. After the salt solution I was completely pumped into the reactor, a 2 mol / L NaOH solution was slowly pumped into the reaction system using a peristaltic pump to control the pH value to 7, and stirred thoroughly for 30 minutes. The above system was then reacted at 108°C for 12 hours to obtain a mixed slurry II.
[0071] After the reactor was cooled to room temperature, the mixed slurry II was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide, anhydrous ethanol and ultrapure water (V:V:V = 1:1:1) to obtain NH2-Mn 0.75 Fe 0.2 Nb 0.015 Zn 0.01 V 0.025 -MOF precursors.
[0072] 2. Synthesis of in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate cathode materials
[0073] According to the molar ratio of Li:P:(Fe+Mn+Nb+Zn+V)=1.05:1:1, lithium dihydrogen phosphate, lithium carbonate, NH2-Mn 0.75 Fe 0.2 Nb 0.015 Zn 0.01 V 0.025 -MOF precursor, and dispersed in a mixed solution of ethanol and ultrapure water (V:V = 1:1) to prepare a slurry with a solid content of 38%, and the mixed slurry was fully ground in a sand mill to a slurry particle size of 0.28 μm ≤ D 50 When the particle size is less than 0.3 μm, the slurry is transferred to the spray drying equipment. The spray drying system is set with an inlet temperature of 240°C and an outlet temperature of 110°C. According to the outlet temperature and the particle size of the discharge (22 μm ≤ D 50 The spray powder was placed in a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content less than 10ppm), and heated to 500℃ for 6h at a heating rate of 2.3℃ / min, and then heated to 680℃ for 9h.
[0074] After the nitrogen atmosphere box furnace is naturally cooled to room temperature, the sintered powder is subjected to air flow pulverization and then sieved using a sieve to obtain the in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate positive electrode material.
[0075] Comparative Example 1
[0076] The difference between Comparative Example 1 and Example 1 is that the prepared lithium manganese iron phosphate material does not contain doped metal elements, and specifically comprises the following steps:
[0077] 1.NH2-Mn 0.6 Fe 0.4 -Synthesis of MOF
[0078] First, add 6L of a mixed solution of dimethyldiformamide and 6L of anhydrous ethanol into a high-efficiency sealed synthesis reactor, slowly add 10mol of 2-aminoterephthalic acid and 0.5mol of hexadecyltrimethylammonium bromide into the reactor, introduce nitrogen protective gas, and stir at 100°C and 600rpm for 20min to prepare the bottom liquid in the reactor.
[0079] Secondly, under a nitrogen protective atmosphere, 6 mol of manganese chloride tetrahydrate and 4 mol of ferric chloride hexahydrate were slowly added to a mixed solution of 6 L of dimethyldiformamide, 6 L of anhydrous ethanol and 6 L of ultrapure water, and stirred at room temperature until completely dissolved to prepare manganese and iron salt solution I. The above salt solution I was slowly pumped into the reactor using a peristaltic pump. After the salt solution I was completely pumped into the reactor, a 2 mol / L NaOH solution was slowly pumped into the reaction system using a peristaltic pump to control the pH value to 7.5, and stirred thoroughly for 30 minutes. The above system was then reacted at 100°C for 12 hours to obtain a mixed slurry II.
[0080] After the reactor was cooled to room temperature, the mixed slurry II was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide, anhydrous ethanol and ultrapure water (V:V:V = 1:1:1) to obtain NH2-Mn 0.6 Fe 0.4 -MOF precursors.
[0081] 2. Synthesis of in-situ carbon-coated lithium manganese iron phosphate cathode material
[0082] Weigh lithium dihydrogen phosphate, lithium carbonate, NH2-Mn and NH4-Mn in a molar ratio of Li:P:(Fe+Mn)=1.05:1:1. 0.6 Fe 0.4 -MOF precursor, and dispersed in a mixed solution of ethanol and ultrapure water (V:V = 1:1) to prepare a slurry with a solid content of 35%, and the mixed slurry was fully ground in a sand mill to a slurry particle size of 0.28 μm ≤ D 50 When the particle size is less than 0.3 μm, the slurry is transferred to the spray drying equipment. The spray drying system is set with an inlet temperature of 220°C and an outlet temperature of 110°C. According to the outlet temperature and the particle size of the discharge (22 μm ≤ D 50The spray powder was placed in a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content less than 10ppm), and heated to 500℃ for 6h at a heating rate of 3℃ / min, and then heated to 700℃ for 9h.
[0083] After the nitrogen atmosphere box furnace is naturally cooled to room temperature, the sintered powder is subjected to air flow pulverization, and then sieved using a sieve to obtain the in-situ carbon-coated lithium manganese iron phosphate positive electrode material.
[0084] Comparative Example 2
[0085] The difference between Comparative Example 2 and Example 2 is that the prepared lithium manganese iron phosphate material does not contain doped metal elements, and specifically includes the following steps:
[0086] 1.NH2-Mn 0.7 Fe 0.3 -Synthesis of MOF
[0087] First, add 6L of a mixed solution of dimethyldiformamide and 6L of anhydrous ethanol into a high-efficiency sealed synthesis reactor, slowly add 10mol of 2-aminoterephthalic acid and 0.5mol of hexadecyltrimethylammonium bromide into the reactor, introduce nitrogen protective gas, and stir at 100°C and 650rpm for 20min to prepare the bottom liquid in the reactor.
[0088] Secondly, under a nitrogen protective atmosphere, 7 mol of manganese chloride tetrahydrate and 3 mol of ferric chloride hexahydrate were slowly added to a mixed solution of 6 L of dimethyldiformamide, 6 L of anhydrous ethanol and 6 L of ultrapure water in sequence, and stirred at room temperature until completely dissolved to prepare manganese and iron salt solution I. The above salt solution I was slowly pumped into the reactor using a peristaltic pump. After the salt solution I was completely pumped into the reactor, a 2 mol / L NaOH solution was slowly pumped into the reaction system using a peristaltic pump to control the pH value to 7.8, and stirred thoroughly for 30 minutes. The above system was then reacted at 100 ° C for 12 hours to obtain a mixed slurry II.
[0089] After the reactor was cooled to room temperature, the mixed slurry II was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide, anhydrous ethanol and ultrapure water (V:V:V = 1:1:1) to obtain NH2-Mn 0.7 Fe 0.3 -MOF precursors.
[0090] 2. Synthesis of in-situ carbon-coated lithium manganese iron phosphate cathode material
[0091] Weigh lithium dihydrogen phosphate, lithium carbonate, NH2-Mn and NH4-Mn in a molar ratio of Li:P:(Fe+Mn)=1.05:1:1. 0.7 Fe0.3 -MOF precursor, and dispersed in a mixed solution of ethanol and ultrapure water (V:V = 1:1) to prepare a slurry with a solid content of 38%, and the mixed slurry was fully ground in a sand mill to a slurry particle size of 0.28 μm ≤ D 50 When the particle size is less than 0.3 μm, the slurry is transferred to the spray drying equipment. The spray drying system is set with an inlet temperature of 230°C and an outlet temperature of 115°C. According to the outlet temperature and the particle size of the discharge (22 μm ≤ D 50 The spray powder was placed in a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content less than 10ppm), and heated to 500℃ for 6h at a heating rate of 2.3℃ / min, and then heated to 680℃ for 9h.
[0092] After the nitrogen atmosphere box furnace is naturally cooled to room temperature, the sintered powder is subjected to air flow pulverization, and then sieved using a sieve to obtain the in-situ carbon-coated lithium manganese iron phosphate positive electrode material.
[0093] Comparative Example 3
[0094] The difference between Comparative Example 3 and Example 3 is that the prepared lithium manganese iron phosphate material does not contain doped metal elements, and specifically includes the following steps:
[0095] 1.NH2-Mn 0.75 Fe 0.25 -Synthesis of MOF
[0096] First, add 6L of a mixed solution of dimethyldiformamide and 6L of anhydrous ethanol into a high-efficiency sealed synthesis reactor, slowly add 10mol of 2-aminoterephthalic acid and 0.5mol of hexadecyltrimethylammonium bromide into the reactor, introduce nitrogen protective gas, and stir at 750rpm for 20min at 100°C to prepare the bottom liquid in the reactor.
[0097] Secondly, under a nitrogen protective atmosphere, 7.5 mol of manganese chloride tetrahydrate and 2.5 mol of ferric chloride hexahydrate were slowly added to a mixed solution of 6 L of dimethyl diformamide, 6 L of anhydrous ethanol and 6 L of ultrapure water in sequence, and stirred at room temperature until completely dissolved to prepare manganese and iron salt solution I. The above salt solution I was slowly pumped into the reactor using a peristaltic pump. After the salt solution I was completely pumped into the reactor, a 2 mol / L NaOH solution was slowly pumped into the reaction system using a peristaltic pump to control the pH value to 7, and stirred thoroughly for 30 minutes. The above system was then reacted at 108°C for 12 hours to obtain a mixed slurry II.
[0098] After the reactor was cooled to room temperature, the mixed slurry II was filtered to separate the solid and liquid, and washed three times with a mixed solution of dimethyl diformamide, anhydrous ethanol and ultrapure water (V:V:V = 1:1:1) to obtain NH2-Mn 0.7.5 Fe 0.25 -MOF precursors.
[0099] 2. Synthesis of in-situ carbon-coated lithium manganese iron phosphate cathode material
[0100] Weigh lithium dihydrogen phosphate, lithium carbonate, NH2-Mn and NH4-Mn in a molar ratio of Li:P:(Fe+Mn)=1.05:1:1. 0.7.5 Fe 0.25 -MOF precursor, and dispersed in a mixed solution of ethanol and ultrapure water (V:V = 1:1) to prepare a slurry with a solid content of 38%, and the mixed slurry was fully ground in a sand mill to a slurry particle size of 0.28 μm ≤ D 50 When the particle size is less than 0.3 μm, the slurry is transferred to the spray drying equipment. The spray drying system is set with an inlet temperature of 240°C and an outlet temperature of 110°C. According to the outlet temperature and the particle size of the discharge (22 μm ≤ D 50 The spray powder was placed in a graphite sagger and placed in a nitrogen atmosphere box furnace (oxygen content less than 10ppm), and heated to 500℃ for 6h at a heating rate of 2.3℃ / min, and then heated to 680℃ for 9h.
[0101] After the nitrogen atmosphere box furnace is naturally cooled to room temperature, the sintered powder is subjected to air flow pulverization, and then sieved using a sieve to obtain the in-situ carbon-coated lithium manganese iron phosphate positive electrode material.
[0102] Comparative Example 4
[0103] 1. Synthesis of carbon-coated multi-cation-doped lithium manganese iron phosphate cathode materials
[0104] In Comparative Example 4, the precursor NH2-Mn in Example 1 does not need to be synthesized. 0.6 Fe 0.35 Ti 0.01 Co 0.01 Mg 0.03-MOF, directly using lithium carbonate as the lithium source, lithium dihydrogen phosphate as the phosphorus source, manganese chloride tetrahydrate as the manganese source, ferric chloride hexahydrate as the iron source and glucose as the carbon source, ammonium oxalate titanium oxide, cobalt acetate and magnesium chloride as dopants, lithium carbonate, lithium dihydrogen phosphate, manganese chloride tetrahydrate, ferric chloride hexahydrate, ammonium oxalate titanium oxide, cobalt acetate and magnesium chloride are weighed according to the same molar ratio as in Example 1, and mixed with ethanol and ultrapure water (V:V=1:1), and at the same time, glucose with the same mass as the organic ligand in Example 1 is added to the above mixed slurry, and the same parameters as in Example 1 are controlled to carry out grinding, spraying, sintering, crushing and sieving processes to obtain a carbon-coated multi-cation doped lithium manganese iron phosphate positive electrode material.
[0105] Performance Testing
[0106] Particle size test: The particle size of the lithium manganese iron phosphate composite material obtained in the embodiment and the comparative example was tested using a Malvern laser particle size analyzer. The results are shown in Table 1.
[0107] Powder resistance test: The powder resistance of the lithium manganese iron phosphate composite materials obtained in the embodiment and the comparative example was tested by a ST2742B powder resistivity tester. The measured results are shown in Table 1.
[0108] Electrochemical performance test: The lithium iron manganese phosphate composite material provided in the above embodiment and comparative example was mixed with polyvinylidene fluoride and acetylene black in a mass ratio of 80:8:12, and N-methylpyrrolidone was added at a solid content of 30% to homogenize, and then coated, dried, and rolled to obtain a positive electrode sheet; a polypropylene film was used as a diaphragm, a lithium sheet was used as a negative electrode, and 1 mol / L LiPF6 (DEC:EC=1:1Vol%) was used as an electrolyte, and the positive electrode, diaphragm and negative electrode were assembled in sequence to obtain a lithium ion battery. The lithium ion battery was subjected to an electrochemical performance test, and the test conditions were as follows: the charge and discharge tests were carried out at 0.1C and 1C rates at room temperature 25°C, and the results are shown in Table 1.
[0109] Compacted density test: The lithium manganese iron phosphate powder samples prepared in the examples and comparative examples were compacted using a powder compaction density meter with a pressure of 5 T, and their volumes and masses were measured to calculate the compacted density.
[0110] Manganese dissolution test: The inductively coupled plasma test method was used to detect the dissolution amount of Mn in the electrolyte of the batteries assembled with the lithium manganese iron phosphate materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4 after cycling 100 times at a current density of 1C.
[0111] The in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate prepared in Example 1 was characterized by scanning electron microscopy, and the results obtained were as follows: Figure 1 As shown. Figure 1It can be seen that the in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate prepared in Example 1 is in the form of nanoscale particles after airflow crushing, and the particle size is uniform, which is beneficial to shorten the migration path of lithium ions during the charge and discharge process and increase the active sites of electrochemical reactions, thereby improving the comprehensive electrochemical performance of the material.
[0112] Table 1
[0113]
[0114] According to the results in Table 1, the compaction density of the in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate prepared by the present invention is relatively high, reaching 2.46 g / cm 3 As above, the powder resistance is ≤10.42Ω·cm, the conductivity is excellent, the first discharge efficiency is high and the 1C discharge specific capacity is high, the rate performance is good, the manganese dissolution amount is below 88ppm, the material structure stability is excellent, which is conducive to improving the cycle stability performance.
[0115] According to the analysis of Table 1, it can be seen that the first charge / discharge specific capacity of Example 1 at a current density of 0.1C reaches 160.3 / 154.3mAh / g, and the first discharge efficiency is 96.3%; under the same conditions, the first charge / discharge specific capacity of Comparative Example 1 reaches 149.3 / 139.1mAh / g, and the first discharge efficiency is only 93.2%. Compared with the examples, the electrochemical performance is reduced, and Example 2 and Comparative Example 2, Example 3 and Comparative Example 3 all show the same rule. This is because the doping of three different metal cations in Example 1 is uniformly distributed at the atomic level in the lithium manganese iron phosphate lattice, which effectively regulates the electronic structure and structural stability of the lithium manganese iron phosphate, and optimizes the morphology and crystallinity of the nanoparticles, thereby improving the conductivity and charge and discharge capacity of the material.
[0116] It can be seen from Example 1 and Comparative Example 4 that compared with the traditional mixed solid phase sintering method, the manganese dissolution amount of the lithium manganese iron phosphate positive electrode material prepared by the preparation method of the present invention is significantly reduced, the compaction density and conductivity are significantly improved, and the electrochemical performance is significantly improved.
[0117] The above embodiments are preferred experimental methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate, characterized in that: The following steps are involved: S1. In an inert atmosphere, dissolving an iron source, a manganese source, a doping metal salt A, a doping metal salt B and a doping metal salt C in a solvent to obtain a solution I; S2. In an inert atmosphere, an organic ligand for forming a metal-organic framework, a surfactant and a solvent are uniformly mixed to obtain a solution II; S3. After mixing solution I and solution II, an alkali solution is added to adjust the pH value of the solution to 7-9, reacting in an inert atmosphere to obtain a mixed slurry, and then performing solid-liquid separation and washing to obtain a metal-organic framework precursor; S4. The metal-organic framework precursor obtained in step S3 is mixed with a lithium source and a phosphorus source, subjected to grinding treatment, spray drying, and calcined under an inert atmosphere to obtain in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate; The general formula of the metal-organic framework precursor is Mn x Fe 1-x-a-b-c A a B b C c -MOF, wherein 0<x<1, 0<a<0.04, 0<b<0.04, 0<c<0.04, a+b+c=0.05; A, B, and C are respectively one of the doped metal elements Mg, Ti, V, Co, Ni, Cr, Zn, Cu, Zr, and Nb, and A, B, and C are different from each other.
2. The preparation method according to claim 1, characterized in that: The general formula of the metal-organic framework precursor is Mn x Fe 1-x-a-b-c A a B b C c -MOF, wherein 0<x<1, 0<a<0.04, 0<b<0.04, 0<c<0.04, a+b+c=0.05; A, B, C are respectively one of the doped metal elements Mg, Ti, V, Co, Zn, Nb, and A, B, C are different from each other.
3. The preparation method according to claim 1, characterized in that: The organic ligand in step S2 is one or more of 4-aminobenzoic acid, 2-aminoterephthalic acid, melamine, imidazole, triazole, benzimidazole, ethylenediamine, ethylenediaminetetraacetic acid, triethylamine, nitrogen tetroxide, 2,2'-bipyridine, 2,4'-bipyridine, 1,10-phenanthroline, 2,6-pyridinedicarboxylic acid, and triethylenediamine.
4. The preparation method according to claim 1, characterized in that: In step S4, the molar ratio of the lithium source, the phosphorus source and the metal source in the metal-organic framework precursor is Li:P:(Fe+Mn+A+B+C)=0.95-1.15:0.95-1.15:
1.
5. The preparation method according to claim 1, characterized in that: The calcination treatment in step S4 is to heat to 350-550° C. at a heating rate of 0.5-20° C. / min for low temperature sintering, and then heat to 650-950° C. for high temperature sintering.
6. The preparation method according to claim 1, characterized in that: The reaction temperature in step S3 is 80-120°C.
7. The in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate prepared as claimed in any one of claims 1 to 6.
8. The in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate according to claim 7, characterized in that: The compaction density of the in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate is ≥2.46 g / cm 3 , powder resistance ≤10.42Ω·cm.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the in-situ carbon-coated multi-cation-doped lithium manganese iron phosphate as described in claim 7 or 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Preparation method for synthesizing doped lithium manganese phosphate / carbon composite material based on mixed metal organic framework
CN112952058A
Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN117199350A
Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN118419887A
Multi-position co-doped lithium iron manganese phosphate composite material, preparation method therefor and secondary battery
WO2024114174A1
Cited By
Three-dimensional porous lithium iron manganese phosphate positive electrode material and preparation method thereof
CN121757831A